Influence of the Type of Delivery, Use of Oxytocin, and Maternal Age on POU5F1 Gene Expression in Stem Cells Derived from Wharton's Jelly within the Umbilical Cord. (14th December 2019) - Gil-Kulik, Paulina; Chomik, Piotr; Krzyżanowski, Arkadiusz; Radzikowska-Büchner, Elżbieta; Maciejewski, Ryszard; Kwaśniewska, Anna; Rahnama, Mansur; Kocki, Janusz
Abstract : The paper presents an evaluation of the POU5F1 gene expression in mesenchymal stem cells derived from Wharton's jelly within the umbilical cord, collected from 36 patients during labor. The study is the first one to show that the expression of POU5F1 in mesenchymal stem cells has been dependent on maternal age, birth order, route of delivery, and use of oxytocin. Our research proves that the POU5F1 gene expression in mesenchymal stem cells decreases with each subsequent pregnancy and delivery. Wharton's jelly stem cells obtained from younger women and during their first delivery, as well as patients treated with oxytocin, show higher POU5F1 gene expression when compared with the subsequent deliveries. This leads to a conclusion that they are characterized by a lower level of differentiation, which in turn results in their greater plasticity and greater proliferative potential. Probably, they are also clinically more useful.